Potency of secondary metabolites of Trichoderma asperellum and Pseudomonas fluorescens in the growth of cocoa plants affected by vascular streak dieback - MANIPPO SIMAMORA; MOHAMMAD BASYUNI; Lisnawita Lisnawita (Society for Indonesian Biodiversity, 2021)
Abstract. Simamora M, Basyuni M, Lisnawita. 2021. Potency of secondary metabolites of Trichoderma asperellum and Pseudomonas fluorescens in the growth of cocoa plants affected by vascular streak dieback. Biodiversitas 22: 2542-2547. Vascular streak dieback (VSD) is the main disease in cocoa caused by Oncobasidium theobromae. Using secondary metabolites of Trichoderma asperellum and Pseudomonas fluorescens is one of the methods to control disease in cocoa plants. The aim of this research is to evaluate the potency of secondary metabolites of T. asperellum and P. fluorescens to control VSD and study its effect on the growth of cocoa plants. The study used a non-factorial, completely randomized design (CRD) with eight treatments and four replications. The secondary metabolites were applied every week for ten times. The results showed that the secondary metabolites of T. asperellum and P. fluorescens were effective in controlling VSD. The combination of organic fertilizer and secondary metabolite of P. fluorescens and T. asperellum as found to be the best treatment to increase cocoa growth and the number of shoots increased by 43.58 shoots